PERCEPTIONS OF POSTPARTUM WOMEN ABOUT EDUCATIONAL PRACTICES DEVELOPED IN A NORMAL BIRTH CENTER: A DESCRIPTIVE-EXPLORATORY STUDY - Silva, Clemilda Alves da; Rodrigues, Diego Pereira; Alves, Valdecyr Herdy; Silva, Sílvia Éder Dias Da; Carneiro, Márcia Simão; Parente, Andressa Tavares; Moura, Letícia Diogo de Oliveira (Cogitare Enfermagem, 2022)
Objective: to understand the meanings of postpartum women about the educational practices developed in a Normal Birth Center. Method: descriptive-exploratory study, of qualitative approach, with 15 postpartum women assisted at the Haydeê Pereira Sena Normal Childbirth Center, in the metropolitan region of Pará, Brazil. Semi structured interviews were used from August to November 2020. Data were transcribed and submitted to content analysis in the thematic modality. Results: it was found that the activities developed by the nurse midwives promote a link to the visibility of the site as a service that seeks to welcome and support women, ensuring greater tranquility, confidence, and respect at the time of birth. Conclusion: the results translate the need to encourage educational practices to ensure rights and respect for women, such as quality assistance, a welcoming environment, aggregating tranquility, and confidence for normal birth. Thus, it contributes effectively to the practice of obstetric nursing with direct impact on the care of women and families.